Perancangan UI/UX Pada Website Ruang Rindu Dengan Metode Design Thinking - Mukti, Kharisma Tara; Febrita, Ruth Ema; Suardinata, I Wayan (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2024)
"Ruang Rindu" is a website administered by the Department of Social Affairs and Empowerment of Women and Family Planning in Banyuwangi Regency. It serves as the focal point for various social programs. The services offered cover both offline and online reporting and consultation. Consultation can be conducted in person at the department's office or via WhatsApp for online consultations. This dual consultation service setup allows users to choose the method that suits their needs best. However, there are challenges with both offline and online consultations. Offline consultations often face issues with queues and waiting times, while online consultations raise concerns about user privacy and data security on WhatsApp. To address these challenges, the UI/UX design team at "Ruang Rindu" utilized the design thinking approach to develop and enhance both offline and online consultation features. The research resulted in the creation of six interface designs. Through testing and analysis using the MAUS (Maze Usability Score) method, a score of 80 was achieved, indicating moderate usability. Similarly, the SUS method yielded a score of 69.25, suggesting a moderate level of user experience. Overall, the "Ruang Rindu" website was found to be acceptable to the public. Key areas explored in this research include UI/UX, Design Thinking, MAUS, and SUS.